Ready or Not, Patients Will Present: Improving Urban Pandemic Preparedness. (16th June 2021) - Madad, Syra; Moskovitz, Joshua; Boyce, Matthew R; Cagliuso, Nicholas V.; Katz, Rebecca
ABSTRACT: Over the past century, society has achieved great gains in medicine, public health, and health-care infrastructure, particularly in the areas of vaccines, antibiotics, sanitation, intensive care and medical technology. Still, despite these developments, infectious diseases are emerging at unprecedented rates around the globe. Large urban centers are particularly vulnerable to communicable disease events, and must have well-prepared response systems, including on the front-line level. In November 2018, the United States' largest municipal health-care delivery system, New York City Health + Hospitals, hosted a half-day executive-level pandemic response workshop, which sought to illustrate the complexity of preparing for, responding to, and recovering from modern-day infectious diseases impacting urban environments. Attendees were subjected to a condensed, plausible, pandemic influenza scenario and asked to simulate the high-level strategic decisions made by leaders by internal (eg, Chief Medical Officer, Chief Nursing Officer, and Legal Affairs) and external (eg, city, state, and federal public health and emergency management entities) partners across an integrated system of acute, postacute, and ambulatory sites, challenging players to question their assumptions about managing the consequences of a highly pathogenic pandemic.